Taste : the story of Britain through its cooking - Colquhoun, Kate, 1964- (London : Bloomsbury, 2007)
Chronicles the social history of Britain through the evolution of its food, tracing the development of aristocratic tastes and street food across the country from pre-Roman times to the present day.
Includes bibliographical references (p. [417]-442) and index.
Keywords: Food habits -- Great Britain -- History; Cooking, British -- History; Cooking, British; Food habits -- Great Britain; British cooking -- History; Eating customs -- Great Britain -- History